Rancang Bangun Pelaporan Keuangan Berbantuan Aplikasi SI APIK - Maria Maria; Choiruddin Choiruddin; Yevi Dwitayanti; Desi Indriasari (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play a meaningful role in the Indonesian economy, sources of employment, and income. The development and sustainability of this type of entity, become the government's top priority in maintaining economic stability. Devotion activities on the design of MSME financial statements using SI APIK application for MSMEs of Bakery Tanjung Enim, Muara Enim in South Sumatera. This activity provides education to business owners about the importance of financial statements. Approach used insolving the problem is participatory methode. The results showed that the SI APIK application made it easier for MSMEs of Bakery Palace to meet the needs of its accounting system. Business owners do not need to bother in compiling financial statements because the recording on the SI APIK application will automatically produce financial statements as needed.